A Reformation sourcebook: documents from an age of debate - Bruening, Michael W. (University of Toronto Press, 2017)
"This sourcebook aims to present the debates of the Reformation era through a range of primary source documents. To do this effectively, the author has arranged the texts in groups rather than individually, for example, on the Indulgence Controversy, Luther's Sermon on Indulgences and Grace is immediately followed by Johann Tetzel's Rebuttal. To help students engage with the primary sources, the author has written an essay on how to read a primary source. Historical background is provided at the beginning of each chapter. Each group of primary sources is described and focus questions are provided. Each chapter concludes with further reading suggestions. A map of Europe at the time of the Reformation is included."--